THE RENTABILITY OF INSURANCE COMPANIES IN INDONESIA STOCK EXCHANGE DEPENDS ON WORKING CAPITAL AND ITS ACTIVITIES - Buniarto, Edwin Agus (Acta Scientiae et Intellectus, 2024)
The purpose of this study was to analyze the level of influence between working capital and rentability ratios activity against insurance companies registered in Indonesia stock exchange, either partially or simultaneously. Samples were secondary data from the financial statements of 12 insurance companies registered in the Indonesian stock exchange in the last three years, in order to obtain the number of 36 samples. It was analyzed by linear regression and using tools SPSS software. The simultaneous and variable working capital resulted in significant effect on the activity ratio rentability of companies with a determination coefficient of 0.697. Partially, variable working capital and ratio of activity have significant effect on rentability with a regression coefficient of 0.582 and 0.483 respectively.